A composite cross-linked polybenzimidazole membrane, a preparation method and use thereof

CN117954662BActive Publication Date: 2026-10-23SHANGHAI INST OF SPACE POWER SOURCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311749030.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2026-10-23
Estimated Expiration
2043-12-19

AI Technical Summary

Technical Problem

[0005]本发明的目的是解决PBI作为高温质子交换膜机械性能及质子电导性不足的问题,提供一种用于高温质子交换膜的新型交联聚苯并咪唑复合膜,不仅具有良好的热力学性能、机械性能和高质子电导率,还具有优异的尺寸稳定性,在高温质子交换膜燃料电池领域中具有良好的应用前景

Benefits of technology

1)本发明通过交联改性,向聚苯并咪唑中引入氨基金属有机框架材料,使得复合膜的质子传导率得以提高。氨基金属框架材料(NH2-MIL101)为刚性多孔无机材料,不仅可以利用其多孔结构吸附磷酸,而且由于其刚性结构,限制聚合物链的移动,可以降低复合膜掺杂磷酸后的溶胀率。另外,NH2-MIL101上含有氨基,存在碱性N原子可以与磷酸分子发生酸碱相互作用,促进磷酸吸收,提高质子电导率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117954662B_ABST
    Figure CN117954662B_ABST
Patent Text Reader

Abstract

This invention discloses a composite crosslinked polybenzimidazole membrane, its preparation method, and its applications. The method includes: Step S1, using OPBI as the matrix material and NH2-MIL101 as the inorganic dopant to prepare an inorganic doping solution; Step S2, mixing the inorganic doping solution with the crosslinking agent FPOSS and then forming a membrane by casting; Step S3, subjecting the resulting membrane to high-temperature treatment to allow the OPBI and FPOSS to crosslink, thereby obtaining the composite crosslinked polybenzimidazole membrane. The preparation process of this invention is simple, the raw material cost is low, and the prepared composite crosslinked membrane, after being doped with phosphoric acid, exhibits advantages such as strong proton conductivity and good mechanical properties, showing broad application prospects in high-temperature proton exchange membrane fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials and fuel cell technology, and relates to a composite cross-linked polybenzimidazole membrane, its preparation method and uses. Background Technology

[0002] High-temperature proton exchange membrane fuel cells (HT-PEMFCs) have been extensively studied due to their environmental friendliness, high energy conversion efficiency, and wide range of applications. Compared with traditional commercial low-temperature fuel cells (LT-PEMFCs), HT-PEMFCs offer many advantages due to their operating temperature exceeding 100°C. These include enhanced catalyst CO tolerance, accelerated electrode reaction kinetics, simplified hydrothermal management, and improved catalytic efficiency.

[0003] With increasing attention being paid to HT-PEMFC, its core component, the high-temperature proton exchange membrane (HT-PEM), has been extensively studied. Polybenzimidazole (PBI) is an engineering plastic with excellent thermal stability and mechanical strength. Due to its unique thermal stability and mechanical properties, PBI has been selected as the matrix material for HT-PEM, but it still needs to be doped with phosphoric acid (PA) before it can be formally applied in fuel cells. PA-doped PBI membranes (PA-PBI) stand out among candidate proton exchange membrane (PEM) materials due to their excellent proton conductivity and stability under high-temperature anhydrous conditions. Studies have shown that under anhydrous conditions, proton conduction in the PA-PBI system mainly follows the Grotthuss conduction mechanism, that is, protons are hopping and conducting in the hydrogen bond network of PA-PBI. A high level of phosphoric acid doping (ADL) can achieve better proton conductivity. However, high ADL also causes two major problems: (1) Decreased mechanical properties. A large number of PA molecules enter the polymer chain, which will destroy the original hydrogen bond interaction, weaken the intermolecular interaction force, and cause a significant deterioration in mechanical properties. (2) PA leaching. Studies have shown that during the operation of HT-PEMFC, PA molecules migrate and are lost under the influence of water molecules. The proton conductivity decreases with the loss of PA, which in turn affects the overall performance of the battery. This hinders its practical application in HT-PEMFC.

[0004] Therefore, the preparation of PBI films with good mechanical properties and high proton conductivity is receiving increasing attention. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of PBI as a high-temperature proton exchange membrane in terms of mechanical properties and proton conductivity, and to provide a novel cross-linked polybenzimidazole composite membrane for high-temperature proton exchange membranes. This membrane not only possesses excellent thermodynamic and mechanical properties and high proton conductivity, but also exhibits superior dimensional stability, and has promising application prospects in the field of high-temperature proton exchange membrane fuel cells.

[0006] To achieve the above objectives, the present invention provides a method for preparing a composite crosslinked polybenzimidazole membrane, comprising: Step S1: Using OPBI as the matrix material and NH2-MIL101 as the inorganic dopant, an inorganic doping solution is prepared by blending. Step S2: After the inorganic doping solution is mixed with the crosslinking agent FPOSS, a film is formed by casting. Step S3: The obtained membrane is subjected to high temperature treatment to crosslink OPBI and FPOSS to obtain a composite crosslinked polybenzimidazole membrane (I). NH2-MIL-101 represents an amino-metal framework material with the following structure: OPBI represents aryl ether polybenzimidazole, with the following structure: FPOSS stands for heptadecafluorodecyltrimethoxysilane, with the following structure: The synthetic route of the composite crosslinked polybenzimidazole membrane (I) is as follows: .

[0007] Optionally, the mass ratio of OPBI to NH2-MIL-101 is 10:3.

[0008] Optionally, the quality ratio of FPOSS to OPBI is 2-8%.

[0009] Optionally, in step S1, NH2-MIL101 is dissolved in a polar aprotic solvent to obtain a homogeneous solution, and then OPBI is added and blended to obtain an inorganic doped solution.

[0010] Optionally, the polar aprotic solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, or dimethyl sulfoxide.

[0011] Optionally, in step S3, before the high-temperature treatment, the membrane obtained in step S2 is also dried to remove the solvent.

[0012] Optionally, the high-temperature treatment refers to treatment at 60-100℃ for 12-24 hours or treatment at 150-170℃ for 1-2 hours.

[0013] Optionally, the process also includes step S4: immersing the composite cross-linked polybenzimidazole membrane obtained in step S3 in an inorganic acid for 12-36 hours at a temperature of 60-80°C to obtain the condensation structure of the cross-linking agent.

[0014] Another object of the present invention is to provide a composite crosslinked polybenzimidazole membrane prepared by the above method. The composite crosslinked polybenzimidazole membrane (I) is denoted as xFPOSS-30MN-OPBI, wherein x represents the weight percentage of the crosslinking agent in the crosslinked membrane × 100, and x is 2~8; the mass ratio of NH2-MIL-101 to OPBI is 3:10; and the mass ratio of FPOSS to OPBI is 2-8%.

[0015] Another object of the present invention is to provide an application of the above-described composite cross-linked polybenzimidazole membrane, wherein the composite cross-linked polybenzimidazole membrane, after being soaked in phosphoric acid, is used as a high-temperature proton exchange membrane for use in high-temperature proton exchange membrane fuel cells.

[0016] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: 1) This invention introduces an amino-metal-organic framework material into polybenzimidazole through crosslinking modification, thereby improving the proton conductivity of the composite membrane. The amino-metal framework material (NH4+) 2- MIL101 is a rigid porous inorganic material. Its porous structure not only allows for the adsorption of phosphoric acid, but its rigid structure also restricts polymer chain movement, reducing the swelling rate of the composite film after phosphoric acid doping. Additionally, NH... 2- MIL101 contains an amino group, and the presence of a basic nitrogen atom can interact with phosphate molecules through acid-base interactions, promoting phosphate absorption and increasing proton conductivity.

[0017] 2) This invention also uses heptadecafluorodecyltrimethoxysilane (FPOSS) as a crosslinking agent, utilizing its hydrolysis properties to form a silane crosslinked network structure in the composite membrane. Phosphoric acid is adsorbed onto the surface of the silane crosslinked network structure through electrostatic interactions, thereby enabling the composite membrane to obtain higher proton conductivity. Simultaneously, the silane crosslinked network structure also enhances the mechanical strength of the composite membrane. Furthermore, heptadecafluorodecyltrimethoxysilane (FPOSS) contains a large number of fluorine groups. Therefore, the silane crosslinked network structure contains a large number of fluorine groups, which can improve the oxidative stability of the composite crosslinked membrane.

[0018] 3) The novel composite crosslinked membrane of the present invention is suitable for mass production. The crosslinking process is very simple and suitable for large-scale industrial production. Furthermore, the high-temperature proton exchange membrane of polybenzimidazole crosslinked with fluorine-containing crosslinking agent prepared by the invention exhibits excellent performance when applied to high-temperature proton exchange membrane fuel cells. Attached Figure Description

[0019] Figure 1 The graph shows the phosphoric acid absorption and anti-swelling properties of the fluorinated crosslinking agent-crosslinked polybenzimidazole high-temperature proton exchange membrane materials prepared in Examples 1-4 and the polybenzimidazole membrane prepared in Comparative Example 1 after immersion in 85wt% phosphoric acid at 100℃ for 3 hours.

[0020] Figure 2 The graphs show the proton conductivity of the fluorinated crosslinking agent-crosslinked polybenzimidazole high-temperature proton exchange membrane materials prepared in Examples 1-4 and the polybenzimidazole membrane prepared in Comparative Example 1 under non-humidification conditions in the range of 110-180°C.

[0021] Figure 3 The graph shows the fuel cell performance of the fluorinated crosslinking agent-crosslinked polybenzimidazole high-temperature proton exchange membrane materials prepared in Examples 1-4 and the polybenzimidazole membrane prepared in Comparative Example 1 under hydrogen-air conditions at 160°C without humidification.

[0022] Figure 4 The infrared spectra of the fluorinated crosslinking agent-crosslinked polybenzimidazole high-temperature proton exchange membrane materials prepared in Examples 1-4, and those of Comparative Example 1 and the crosslinking agent are shown. Detailed Implementation

[0023] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] For HT-PEM, traditional crosslinking methods can effectively improve the mechanical properties of PBI membranes because strong bonds are formed between PBI molecules. However, these strong bonds also hinder PA absorption, leading to a decrease in proton conductivity.

[0025] MOFs are used to construct proton transport channels in HT-PEMs, reducing the dependence of proton conduction on PA and improving the proton conductivity of the composite membrane, thereby enhancing the proton conductivity.

[0026] To address the shortcomings of existing technologies, this invention incorporates an amino-metal framework material (NH2-MIL101) as a filler into a composite membrane and uses a novel crosslinking agent, heptadecafluorodecyltrimethoxysilane (FPOSS), to crosslink with PBI to prepare a polybenzimidazole composite crosslinked proton exchange membrane material. The high-temperature polymer membrane prepared by this method not only has good thermodynamic properties, mechanical properties, and high proton conductivity, but also excellent dimensional stability.

[0027] The preparation method of a composite crosslinked polybenzimidazole membrane (I) of the present invention comprises: Step S1: Using OPBI as the matrix material and NH2-MIL101 as the inorganic dopant, an inorganic doping solution is prepared by blending.

[0028] Specifically, NH2-MIL-101 is dissolved in a polar aprotic solvent to obtain a homogeneous solution, and then OPBI is added and blended to obtain an inorganic doped solution. The mass ratio of OPBI to NH2-MIL-101 is 10:3. The polar aprotic solvent is at least one selected from N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, or dimethyl sulfoxide.

[0029] Step S2: After the inorganic doping solution is mixed with the crosslinking agent FPOSS, a film is formed by casting.

[0030] The quality ratio of FPOSS to OPBI is 2-8%.

[0031] Step S3: The obtained membrane is subjected to high temperature treatment to crosslink OPBI and FPOSS to obtain a composite crosslinked polybenzimidazole membrane (I).

[0032] In step S3, before the high-temperature treatment, the membrane obtained in step S2 is also dried to remove the solvent. For example, an oven is used, and the temperature is maintained at 60°C for 12 hours.

[0033] The high-temperature treatment refers to treatment at 60-100℃ for 12-24 hours to dry the residual solvent in the membrane; then, treatment at 150-170℃ for 1-2 hours to allow the membrane substrate and crosslinking agent to undergo a crosslinking reaction. As an example, the high-temperature treatment refers to treatment at 80℃ for 12 hours and treatment at 160℃ for 1 hour.

[0034] NH2-MIL-101 represents an amino-metal framework material with the following structure: OPBI represents aryl ether polybenzimidazole, with the following structure: FPOSS stands for heptadecafluorodecyltrimethoxysilane, with the following structure: The synthetic route of the composite crosslinked polybenzimidazole membrane (I) is as follows: .

[0035] The method of the present invention further includes step S4: immersing the composite cross-linked polybenzimidazole membrane obtained in step S3 in an inorganic acid for 12-36 hours at a temperature of 60-80°C to obtain the condensation structure of the cross-linking agent.

[0036] The composite crosslinked polybenzimidazole membrane (I) prepared by this invention can be designated as xFPOSS-30MN-OPBI, where x represents the weight percentage of the crosslinking agent in the crosslinked membrane × 100. In this invention, x is 2~8. The mass ratio of NH2-MIL-101 to OPBI is 3:10; the mass ratio of FPOSS to OPBI is 2-8%.

[0037] The composite cross-linked polybenzimidazole membrane of the present invention is used as a high-temperature proton exchange membrane in high-temperature proton exchange membrane fuel cells.

[0038] Example 1: Preparation of 2FPOSS-OPBI high-temperature proton exchange membrane material The mass ratio of heptadecafluorodecyltrimethoxysilane (FPOSS) to imidazole in polybenzimidazole is controlled to be 2:100, that is, 2% by mass of heptadecafluorodecyltrimethoxysilane (FPOSS) is added.

[0039] First, 30% of the amino metal framework material (NH2-MIL-101) was added to an N-methylpyrrolidone solution and ultrasonically stirred to dissolve and disperse it evenly, obtaining a mixed solution. Then, aryl ether polybenzimidazole (OPBI) was added to the above mixed solution and heated and stirred at 80°C for 4 hours to dissolve it, finally obtaining an inorganic doped solution with an OPBI mass fraction of 8 wt%. Next, 2% (by mass) of the crosslinking agent heptadecafluorodecyltrimethoxysilane (FPOSS) was added to the above inorganic doped solution and heated and stirred at 80°C for 1 hour. The resulting mixed solution was poured onto a 20×20 cm glass plate, and a scraper was used to uniformly form a film on the glass plate. The film was dried completely in a 60°C oven, and then treated in a vacuum oven at 80°C for 12 hours and 160°C for 1 hour to complete the reaction between PBI and the crosslinking agent. After the reaction was complete, all the dried films were peeled off and immersed in a 1M H2SO4 solution at 80°C for 24 hours to obtain the condensation structure of the crosslinking agent. All membranes were then rinsed multiple times with deionized water and dried at 130°C for 24 hours. xFPOSS-30MN-OPBI membranes were prepared, where x represents the weight percentage of the crosslinking agent in the crosslinked membrane. The resulting composite crosslinked membrane was immersed in 85wt% phosphoric acid at 100°C for 3 hours and then removed to obtain the desired composite high-temperature proton exchange membrane.

[0040] Example 2 Example 2 is a high-temperature proton exchange membrane of polybenzimidazole crosslinked with a fluorinated crosslinking agent. The difference from Example 1 is that the mass ratio of heptadecafluorodecyltrimethoxysilane (FPOSS) added is 4%.

[0041] Example 3 Example 3 is a high-temperature proton exchange membrane of polybenzimidazole crosslinked with a fluorinated crosslinking agent. The difference from Example 1 is that the mass ratio of heptadecafluorodecyltrimethoxysilane (FPOSS) added is 6%.

[0042] Example 4 Example 4 is a high-temperature proton exchange membrane of polybenzimidazole crosslinked with a fluorinated crosslinking agent. The difference from Example 1 is that the mass ratio of heptadecafluorodecyltrimethoxysilane (FPOSS) added is 8%.

[0043] Comparative Example 1 Comparative Example 1 is an aryl ether type polybenzimidazole (OPBI) high-temperature proton exchange membrane, which differs from Example 1 in that it does not contain an amino metal-organic framework material. The specific preparation process is as follows: OPBI was added to an N-methylpyrrolidone solution and heated and stirred at 80°C for 4 hours to dissolve it uniformly, yielding a homogeneous and transparent solution with a mass fraction of 8%. A film was formed by casting the homogeneous solution onto a glass plate and heating at 60°C for 12 hours to evaporate the solvent, thus obtaining a polybenzimidazole high-temperature proton exchange membrane. The membrane was then immersed in 85 wt% phosphoric acid at 100°C for 3 hours to obtain the desired high-temperature proton exchange membrane.

[0044] Comparative Example 2 Comparative Example 2 is a high-temperature proton exchange membrane doped with an amino-metal-organic framework (MOF), specifically a polybenzimidazole (PMB) membrane, wherein the MOF material accounts for 30% of the total material. The specific preparation process of the composite membrane is shown below: The mass ratio of amino-metal framework material (NH2-MIL-101) to imidazole in polybenzimidazole was controlled at 3:10, i.e., 30% by mass of amino-metal framework material (NH2-MIL-101) was added. First, amino-metal framework material (NH2-MIL-101) was added to an N-methylpyrrolidone solution and ultrasonically stirred until it dissolved and dispersed evenly. Then, polybenzimidazole was added to the above mixture and heated and stirred at 80°C for 4 hours to dissolve it, finally obtaining an inorganic doped solution with a PBI mass fraction of 8 wt%. A film was formed using a casting method, casting the homogeneous solution onto a glass plate and heating at 60°C for 12 hours to evaporate and remove the solvent, obtaining an inorganically doped polybenzimidazole high-temperature proton exchange membrane. The inorganic doped membrane was then immersed in 85 wt% phosphoric acid at 100°C for 3 hours and removed to obtain the desired composite high-temperature proton exchange membrane.

[0045] The composite films with different doping amounts obtained in Examples 1-3 and Comparative Examples 1-2 were subjected to the following offline and online tests after being treated with phosphoric acid.

[0046] Referring to GB / T 20042.3-2022, the swelling rate of the obtained high-temperature proton exchange membrane was tested. Specific operating conditions were as follows: under constant temperature and humidity conditions of 23℃±2℃ and 50%±5%, the initial length L0 and initial width W0 of the sample were measured with calipers, and the thickness d0 of the sample was measured with a thickness gauge. The sample was then immersed at a constant temperature of 100℃ and a phosphoric acid concentration of 85% for 3 hours. The length L and width W of the sample were measured with calipers, and the thickness d of the sample was measured with a thickness gauge.

[0047] According to GB / T 20042.3-2022, the proton conductivity of the obtained high-temperature proton exchange membrane was tested. The specific operating conditions were: the temperature was 110℃-180℃ and the humidity was 0%, and the conductivity testing device was connected to the electrochemical impedance spectroscopy instrument.

[0048] According to GB / T 20042.5-2009, the polarization curve of the obtained high-temperature proton exchange membrane fuel cell was tested. The specific operating conditions were: single cell operating temperature of 160℃, anode feed of pure hydrogen, cathode feed of atmospheric pressure air, and cathode / anode feed ratio of 4 / 1.

[0049] Test results are attached to the instruction manual. Figure 1-3 : See Figure 1 The phosphoric acid doping rate and swelling rate of the composite films prepared in Examples 1, 2, 3, and 4 of this invention, and the films prepared in Comparative Examples 1 and 2 were measured. (Source: [Insert data here]) Figure 1 As can be seen, after phosphoric acid doping, the phosphoric acid doping rates of Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 of this invention were measured to be 330.1%, 320.4%, 319.8%, 312.1%, 295.6%, and 238.1%, respectively. The corresponding swelling rates were 217.9%, 215.9%, 197.3%, 167.9%, 155.8%, and 108.5%, respectively. It is evident that compared to the films of Comparative Example 1 and Comparative Example 2, the composite cross-linked films prepared in Examples 1, 2, 3, and 4 of this invention have higher phosphoric acid absorption capacity, and the swelling rate decreases with increasing cross-linking degree.

[0050] See Figure 2 The proton conductivity diagrams of the composite membranes prepared in Examples 1, 2, 3, and 4 of this invention, and the membranes prepared in Comparative Examples 1 and 2, were measured. Figure 2 It can be seen that at 110℃, the proton conductivity of Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 of the present invention was measured to be 0.1609 S / cm. -1 0.1807 S.cm -10.1984 S.cm -1 0.1176S.cm -1 0.0826 S.cm -1 0.1351 S.cm -1 At 160°C, the proton conductivity of Examples 1, 2, 3, and 4 of this invention, as well as Comparative Example 1 and Comparative Example 2, was measured to be 0.2093 S.cm. -1 0.2357S.cm -1 0.2500 S.cm -1 0.1553 S.cm -1 0.1216 S.cm -1 0.1688S.cm -1 At 180°C, the proton conductivity of Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 of this invention was measured to be 0.2126 S·cm. -1 0. 0.2297 S.cm -1 0. 0.2448 S.cm -1 0.1559S.cm -1 0.1231 S.cm -1 0.1646 S.cm -1 Compared to the membrane prepared in Comparative Example 1, the composite cross-linked membranes prepared in Examples 1-4 of this invention exhibit higher proton conductivity and better proton conductivity. Compared to the membrane in Comparative Example 2, the composite cross-linked membranes prepared in Examples 1-3 of this invention exhibit higher proton conductivity and better proton conductivity, while the composite cross-linked membrane prepared in Example 4 of this invention has slightly lower proton conductivity. It is evident that the addition amount of heptadecafluorodecyltrimethoxysilane (FPOSS) is not necessarily better the more it is added; when the addition amount exceeds 6%, the proton conductivity effect deteriorates.

[0051] See Figure 3 The fuel cell performance of the composite membranes prepared in Examples 1, 2, 3, and 4 of this invention, and the membrane prepared in Comparative Example 1, was measured under non-humidified hydrogen-air conditions at 160°C. As can be seen from the graphs, at 0.1 A / cm²... 2 The membrane electrode voltages measured for Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 of the present invention were 0.736 V, 0.724 V, 0.735 V, 0.709 V, 0.695 V, and 0.714 V, respectively. The fuel cell power densities measured for Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 of the present invention were 73.6 mW·cm⁻¹. -2 72.4mW.cm -270.9 mW.cm -2 69.5 mW.cm -2 71.4 mW.cm -2 At 0.5A / cm 2 The membrane electrode voltages measured for Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 of the present invention were 0.6 V, 0.602 V, 0.615 V, 0.572 V, 0.538 V, and 0.595 V, respectively. The fuel cell power densities measured for Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 of the present invention were 300 mW·cm⁻¹. -2 301mW.cm -2 307.5 mW.cm -2 269mW.cm -2 297.5mW.cm -2 At 1.0 A / cm 2 The membrane electrode voltages measured for Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 were 0.491 V, 0.495 V, 0.509 V, 0.456 V, 0.416 V, and 0.486 V, respectively. The fuel cell power densities measured for Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2 were 491 mW·cm⁻¹. -2 495 mW.cm -2 509 mW.cm -2 456 mW.cm -2 416 mW.cm -2 486mW.cm -2 As can be seen, compared with the membrane prepared in Comparative Example 1, the composite crosslinked membranes prepared in Examples 1-4 of this invention have lower membrane electrode polarization losses and higher fuel cell performance. Compared with the membrane in Comparative Example 2, the composite crosslinked membranes in Examples 1, 2, and 3 of this invention have lower membrane electrode polarization losses and higher fuel cell performance, while the composite crosslinked membrane prepared in Example 4 of this invention has higher membrane electrode polarization losses and lower fuel cell performance. It is evident that the amount of heptadecafluorodecyltrimethoxysilane (FPOSS) added is not necessarily better the more it is added; when the addition amount exceeds 6%, the membrane electrode polarization loss of the composite crosslinked membrane increases.

[0052] See Figure 4 Comparing the infrared spectra of OPBI, Examples 1-4 show a difference at 1040 cm⁻¹. -1 There is a distinct Si-O-Si stretching vibration absorption peak at 2844 cm⁻¹, and also at 2844 cm⁻¹. -1 The presence of methylene absorption peaks and these two infrared peaks proves the successful synthesis of the composite cross-linked membrane.

[0053] In summary, this invention introduces an amino-metal-organic framework material into polybenzimidazole through crosslinking modification, thereby improving the proton conductivity of the composite membrane. The amino-metal framework material (NH4+) 2- MIL101 is a rigid porous inorganic material. Its porous structure not only allows for the adsorption of phosphoric acid, but its rigid structure also restricts polymer chain movement, reducing the swelling rate of the composite film after phosphoric acid doping. Additionally, NH... 2- MIL101 contains amino groups, and the presence of Lewis basic nitrogen atoms allows for acid-base interactions with phosphate molecules, promoting phosphate absorption and increasing proton conductivity. Furthermore, this invention uses heptadecafluorodecyltrimethoxysilane (FPOSS) as a crosslinking agent, utilizing its hydrolytic properties to form a silane crosslinked network structure in the composite membrane. Phosphoric acid is adsorbed onto the surface of the silane crosslinked network structure through electrostatic interactions, resulting in higher proton conductivity in the composite membrane. Simultaneously, the silane crosslinked network structure also enhances the mechanical strength of the composite membrane. Moreover, heptadecafluorodecyltrimethoxysilane (FPOSS) contains a large number of fluorine groups; therefore, the silane crosslinked network structure contains a large number of fluorine groups, which can improve the oxidative stability of the composite crosslinked membrane.

[0054] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.

Claims

1. A method for preparing a composite cross-linked polybenzimidazole membrane, characterized in that, Include: Step S1: Using OPBI as the matrix material and NH2-MIL101 as the inorganic dopant, an inorganic doping solution is prepared by blending. Step S2: After the inorganic doping solution is mixed with the crosslinking agent FPOSS, a film is formed by casting. Step S3: The obtained membrane is subjected to high temperature treatment to crosslink OPBI and FPOSS to obtain a composite crosslinked polybenzimidazole membrane (I). NH2-MIL-101 represents an amino-metal framework material with the following structure: ; OPBI represents aryl ether polybenzimidazole, with the following structure: ; FPOSS stands for heptadecafluorodecyltrimethoxysilane, with the following structure: ; The synthetic route of the composite crosslinked polybenzimidazole membrane (I) is as follows: 。 2. The method for preparing the composite cross-linked polybenzimidazole membrane as described in claim 1, characterized in that, The mass ratio of OPBI to NH2-MIL-101 is 10:

3.

3. The method for preparing the composite cross-linked polybenzimidazole membrane as described in claim 1, characterized in that, The quality ratio of FPOSS to OPBI is 2-8%.

4. The method for preparing the composite cross-linked polybenzimidazole membrane as described in claim 1, characterized in that, In step S1, NH2-MIL101 is dissolved in a polar aprotic solvent to obtain a homogeneous solution, and then OPBI is added and blended to obtain an inorganic doped solution.

5. The method for preparing the composite cross-linked polybenzimidazole membrane as described in claim 4, characterized in that, The polar aprotic solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, or dimethyl sulfoxide.

6. The method for preparing the composite cross-linked polybenzimidazole membrane as described in claim 1, characterized in that, In step S3, before the high-temperature treatment, the membrane obtained in step S2 is dried to remove the solvent.

7. The method for preparing the composite cross-linked polybenzimidazole membrane as described in claim 1, characterized in that, The high-temperature treatment refers to treatment at 60-100℃ for 12-24 hours or at 150-170℃ for 1-2 hours.

8. The method for preparing the composite cross-linked polybenzimidazole membrane as described in claim 1, characterized in that, It also includes step S4: placing the composite cross-linked polybenzimidazole membrane obtained in step S3 in an inorganic acid and immersing it at 60-80℃ for 12-36 hours to obtain the condensation structure of the cross-linking agent.

9. A composite cross-linked polybenzimidazole membrane prepared by the method according to any one of claims 1-6, characterized in that, The composite cross-linked polybenzimidazole membrane (I) is denoted as xFPOSS-30MN-OPBI, where x represents the weight percentage of the cross-linking agent in the cross-linked membrane × 100, and x is 2~8; the mass ratio of NH2-MIL-101 to OPBI is 3:10; and the mass ratio of FPOSS to OPBI is 2-8%.

10. The use of the composite crosslinked polybenzimidazole membrane according to claim 9, characterized in that, The composite cross-linked polybenzimidazole membrane, after being soaked in phosphoric acid, serves as a high-temperature proton exchange membrane for use in high-temperature proton exchange membrane fuel cells.

Citation Information

Patent Citations

  • Highly conductive superhydrophobic gas diffusion layer and preparation method thereof

    CN110444769A

  • Polybenzimidazole with cross-linked structure, high-temperature proton exchange membrane and preparation method of high-temperature proton exchange membrane

    CN116284778A